Case report: A rare case of three synchronous colon tumors with metastasis to the left inguinal lymph node - Negrut, Roxana Loriana; Cote, Adrian; Tica, Ovidiu; Maghiar, Adrian Marius (Frontiers in Oncology, 2025)
This study presents a rare case of three synchronous colon tumors with metastasis to the left inguinal lymph node, challenging the conventional understanding of the metastatic pathways and highlighting the exceptional nature of such occurrences. This highlights the importance of considering alternative atypical metastatic routes for the management of colon cancer. A literature search was performed to identify similar cases. Our findings emphasize the need for broader diagnostic evaluations to detect atypical metastasis at early stages. Furthermore, this case highlights the need for potential refinements in follow-up and screening protocols to capture unusual patterns of cancer spread. This case encourages further research into innovative treatments tailored to the unique metastatic behaviors observed in synchronous colon tumors, with a view to improving outcomes in similar cases.